Case report: Chorea and cognitive decline in a young woman: instrumental and genetic assessment of a case originally diagnosed as multiple sclerosis - Dato, Clemente; Micaglio, Emanuele; Moresco, Giada; Rondinone, Ornella; Vitali, Paolo; Pappone, Carlo; Fontana, Laura; Miozzo, Monica; Bet, Luciano (Frontiers in Genetics, 2023)
We describe the case of a young woman affected by debilitating chorea and rapidly progressive cognitive decline. While her original diagnosis was multiple sclerosis, we performed a full instrumental and genetic assessement, though which we identified multiple genetic variants, including a novel variant of the APP gene. We propose some possible mechanisms by which such variants may contribute to neuroinflammation and ultimately lead to this devastating clinical course.